SEJARAH PENGEBOMAN CANDI BOROBUDUR TAHUN 1985: TINJAUAN SEJARAH SOSIAL POLITIK DI INDONESIA - Pratama, Angga Novian; Sodiq, Ibnu; Suryadi, Andy (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2019)
The history of politics in Indonesia, especially Orde Baru is indeed inseparable from the conflict between Islam and the state, especially the problem of ideology. This was seen when the Orde Baru applied a non-aspirational political strategy to Islam, one of them is asas tunggal Pancasila. The inequality of political views with the government caused various reactions and resistance from radical Islamists. One of the incidents is the Borobudur Temple bombing in 1985. The methods used in this study were historical research methods, this is: (1) Heuristics, (2) Source Criticism, (3) Interpretation, and (4) Historiography. The results of this study indicate that there are factors underlying the occurrence of the Borobudur Temple bombing, this is: (1) Political factors, the reactions of various Orde Baru policies which were considered to marginalize Islam, (2) Social factors, the emergence of a sense of injustice conducted by the government in the Tanjung Priok tragedy 1984, (3) Religious and ideological emotional factors, the desire to carry out a revolution like in Iran by revenge for bombing. The handling of the government in this case took two months, until the incident of Pemudi Express Bus exploded which resulted in the arrest of the perpetrators. This bombing resulted in the destruction of nine Borobudur Temple stupas which led to the restoration and improvement of the temple area security system. This incident also had an impact on the tourism, social and political economy in Indonesia.   Keywords: Bombing, Borobudur Temple, Social History